Subsidies and consumer environmental awareness: a systematic review of aspects and impacts / Juliana Mohd Abdul Kadir ... [et al.] - Mohd Abdul Kadir, Juliana; Mhd Noh, Nor Aziedah; Ramli, Ahmad Razi; Hamdan, Rosita (Faculty of Business and Management, 2022)
Supply-side fiscal policy holds that the growth of the country is stimulated through fiscal expansion designed to foster increased production. Subsidies given by the government to producers save many essential industries from higher cost of production thus encouraging them to increase supply of goods and services. On the other hand, subsidies provided to the public have benefitted them from paying higher prices for consumer products thus enhancing their welfare. However, these subsidies and incentives may promote overproduction and encourage overconsumption since cost of production becomes much cheaper after being subsidized. This has consequences on the consumer environmental awareness (CEA) as excessive use of certain products e.g. fuel, may result in environmental pollution. Using a systematic literature review, we explore subsidy and environmental awareness among consumers. We focus on environmental awareness as an interesting issue to bring forward in this research and our study contributes to the existing literature. The results of our study imply that the provision of subsidies on fuels resulted in excessive use of self-transport which has an impact on climate change. However, in other cases, green subsidies do benefit society in general. High environmental awareness can be decisive in influencing green purchasing behaviour, resulting in high demand for green products.